Explorers - Luke, Eric.; Feldman, Edward S.; Dante, Joe.; Bombyk, David, 1952-1989.; Hawke, Ethan; Phoenix, River; Presson, Jason; Peterson, Amanda; Picardo, Robert; Paramount Pictures Corporation (Hollywood, Calif. : Paramount Pictures, 2004)
In their makeshift laboratory, three young boys use an amazing discovery and their ingenuity to build their own spaceship and launch themselves on a fantastic interplanetary journey.
Originally released as motion picture in 1985.
Special features: 2 additional scenes: Wolfgang is bullied [and] Unexpected Thunder Road ride.
Music, Jerry Goldsmith; visual effects, Industrial Light and Magic; executive producer, Michael Finnell.
Cast: Ethan Hawke, River Phoenix, Jason Presson, Amanda Peterson, Robert Picardo.
Rated PG; Canadian home video rating: G.
DVD; widescreen, modifed from its original version; Dolby digital 5.1 surround, Dolby surround.
Keywords: Human-alien encounters -- Drama; Boys -- Drama; Science fiction films; Feature films; Closed captioned